Meaningful score changes for SF-36v2, FACIT-fatigue, and RASIQ in rheumatoid arthritis - Regina Rendas-Baum; Xiaochen Lin; Mark Kosinski; Jakob Bue Bjorner; Marguerite G. Bracher; Wen-Hung Chen (SpringerOpen, 2024)
Abstract Background Interpretation thresholds for patient-reported outcome (PRO) scores are of crucial importance, particularly when interpreting treatment benefit. This study was designed to determine the within-patient meaningful improvement (WPMI) thresholds for the Short-Form 36 Health Survey version 2 (SF-36v2), the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue), and the novel Rheumatoid Arthritis Symptoms and Impact Questionnaire (RASIQ) among patients with rheumatoid arthritis (RA). Methods In this post-hoc analysis, anchor-based and supportive distribution-based methods were used to derive WPMI based on blinded data from all treatment arms in two Phase 2 RA trials with otilimab. Patient's Global Assessment of Disease Activity (PtGA) was the general anchor for all SF-36v2 scales. SF-36 Patient's Global Impression of Status (PGIS), PtGA, and VT03 (an SF-36v2 item) were used as anchors for FACIT-Fatigue. SF-36 PGIS, PtGA, and Patient's Assessment of Arthritis Pain (PAIN) were anchors for RASIQ. Mean change was calculated for the anchor category associated with minimal meaningful improvement from baseline to Week 24 for SF-36v2 and FACIT-Fatigue, and to Week 12 for RASIQ. Sensitivity and specificity were used to evaluate the accuracy of estimated WPMI values. Results For the SF-36v2 physical functioning, role physical, bodily pain, general health, vitality, social functioning, role emotional, and mental health domains, anchor-based estimates of WPMI based on 0-100 scores were 24.5, 24.5, 25.4, 13.6, 21.5, 20.5, 16.9, and 14.3, respectively. Anchor-based WPMI estimates were 9.7 for the Physical Component Summary score and 7.6 for the Mental Component Summary score (using norm-based T-score metric). For FACIT-Fatigue (range 0-52), WPMI estimates ranged from 9.7 to 11.3 points. For RASIQ (range 0-100), anchor-based WPMI was determined as a change between -32.7 and -21.7 points for the Joint Pain scale, -26.7 to -23.7 for the Joint Stiffness scale, and -21.1 to -17.4 for the Impact scale. Conclusions This study derived WPMI thresholds for SF-36v2, FACIT-Fatigue, and RASIQ among patients with RA, using multiple anchors. Derivation of WPMI thresholds for these PRO instruments will enable their broader use in evaluating and interpreting treatment benefit in future RA studies.